PENGARUH PENGGUNAAN E-MODUL BERBASIS ETNOSAINS TERHADAP HASIL BELAJAR SISWA PADA MATERI GAYA DI SEKITAR KITA DI KELAS IV SEKOLAH DASAR - Lestri, Nurya; Safiah, Intan; Fitriani, Suci (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of students in the Naturaland Social Sciences (IPAS) subject "Styles around us" material in grade IV of SDNLampeuneurut. This condition is influenced by the use of non-contextual teachingmaterials, so that learning has not fully integrated science concepts with realphenomena and local wisdom in the student environment. This study aims todetermine the influence of the use of ethnoscience-based e-modules on studentlearning outcomes in the material "Styles around Us" in grade IV of elementaryschool. This study uses a quantitative approach with quasi-experimental design andnonequivalent control group design. The research sample consisted of 56 students,namely class IVA as the experimental class and class IVB as the control classselected through purposive sampling techniques. The research instrument is in theform of a multiple-choice test. Data analysis included N-Gain calculation, normalitytest, homogeneity test and hypothesis test using Independent Samples t-Test. Theresults showed that the average N-Gain of the experimental class was higher thanthat of the control class with a significance value of 0.001 < 0.05. Thus, it can beconcluded that the use of ethnoscience-based e-modules has a significant effect onstudent learning outcomes in the material "Styles Around Us" in grade IV ofelementary school.